Continuous-wave pumping supercontinuum generation in random distributed feedback laser cavity - Lau K.Y.; Suhailin F.H.; Abidin N.H.Z.; Abas A.F.; Alresheedi M.T.; Mahdi M.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Bandwidth; Distributed feedback lasers; Feedback; Fiber lasers; Fibers; Laser resonators; Pumping (laser); Anomalous dispersion; Continuous-wave pumping; Continuous-wave Raman laser; Distributed feedback fiber lasers; Modulation instabilities; Nonlinear mechanisms; Random fibers; Spectral broadening; Supercontinuum generation